Performance analysis of golf: Reflections on the past and a vision of the future - Nic, J. (International Journal of Performance Analysis in Sport, 2009)
Notational analysis of golf involves using either outcome measures, namely scores (hole and round) or process measures which can be independent (e.g.driving distance) or composite (e.g.greens in regulation) elements of the game. Research suggests that there is a relatively large variation in round scores for successive rounds although this paper shows the way in which this finding is interpreted is related to the data sample used. This paper re-analyses previous data to suggest that the most consistent finding is that a bad score on one hole increases the likelihood of a bad score on the subsequent hole irrespective of the standard of the player. Greens in regulation (GIR) along with putting leaders (putts per GIR) have consistently been shown to be the best indicators of overall scoring with driving distance and driving accuracy the others of significance. Here a form chart was used to show how inaccurate these variables (with scrambling added) were as predictors of Tiger Wood's scoring performance during the years 2000 and 2007. It was hence argued that it is only independent elements of the game that need to be analysed to determine the true worth of the different elements e.g.putting, approach shots and driving measures, to scoring ability. It is further argued here, that performance improvement in each element of the game may be related to the availability of relevant performance measures for that element.